2017
DOI: 10.1371/journal.pone.0175629
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high field upper extremity peripheral nerve and non-contrast enhanced vascular imaging

Abstract: ObjectiveThe purpose of this study was to explore the efficacy of Ultra-high field [UHF] 7 Tesla [T] MRI as compared to 3T MRI in non-contrast enhanced [nCE] imaging of structural anatomy in the elbow, forearm, and hand [upper extremity].Materials and methodA wide range of sequences including T1 weighted [T1] volumetric interpolate breath-hold exam [VIBE], T2 weighted [T2] double-echo steady state [DESS], susceptibility weighted imaging [SWI], time-of-flight [TOF], diffusion tensor imaging [DTI], and diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Diffusion‐weighted neurography has been previously described as a technique for brachial plexus MRI evaluation . Diffusion imaging, however, conventionally employs echo‐planar techniques that are inherently susceptible to motion artifact . In a study comparing RT and breath holding for diffusion‐weighted MRI of liver lesions, Kandpal et al reported greater image quality and SNR with prospective RT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion‐weighted neurography has been previously described as a technique for brachial plexus MRI evaluation . Diffusion imaging, however, conventionally employs echo‐planar techniques that are inherently susceptible to motion artifact . In a study comparing RT and breath holding for diffusion‐weighted MRI of liver lesions, Kandpal et al reported greater image quality and SNR with prospective RT .…”
Section: Discussionmentioning
confidence: 99%
“…22 Diffusion imaging, however, conventionally employs echo-planar techniques that are inherently susceptible to motion artifact. 16,23,24 In a study comparing RT and breath holding for diffusion-weighted MRI of liver lesions, Kandpal et al reported greater image quality and SNR with prospective RT. 25 We speculate that an RT approach may similarly reduce motion artifact for brachial plexus DTI sequences.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gong et al performed an attempt on contrast enhanced MRI with low dose of contrast agent through deep learning of AI (Figure 11). By employing the non-contrast MRI and low-contrast MRI as inputs for deep learning, simulated model/algorithm will be predicted based on the obtained signal difference between non-contrast MRI and low-contrast MRI (Raval et al, 2017). Subsequently, this algorithm will be used to synthesize a full does contrast enhanced MRI to verify the formerly set-up full dose MRI.…”
Section: The Role Of Artificial Intelligence For Developing Novel/biomentioning
confidence: 99%
“…As the fabrications of nanoparticle contrast agents focus on optimizing a variety of parameters, with the emerging of AI, the algorithm based on the deep learning will complete all these tasks prior to perform the final optimized experiments for verification, which will save substantial time, efforts and achieve the high resolution MRI (Moser et al, 2017;Raval et al, 2017). Furthermore, for future MRI, it is suggested to employ the convolutional neural networks in AI deep learning to get the multimodal imaging information with high resolution (Figure 14), where the conventional MRI can only achieve single information with the applied high magnetic field (over 7 T) (Donatelli et al, 2018;Henning, 2018;Turing, 2019).…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Technical advances and particularly the availability of higher field strength have significantly improved visualization of peripheral nerves. Recently, morphologic peripheral nerve imaging has been performed at 7 T, 4 7 which substantially enhances the signal-to-noise ratio (SNR) and therefore the achievable spatial resolution, thus improving anatomical depiction of peripheral nerves. In contrast to morphologic sequences, most human peripheral nerve DTI has been implemented at lower field strength, with the exception of one recent attempt at 7 T in 3 healthy participants.…”
mentioning
confidence: 99%